Transparansi Pengadaan Barang/Jasa Di Kantor Layanan Pengadaan Secara Elektronik Kota Makassar - Putra, Cakra Mandala; Muhammadiah, Muhammadiah; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine the innovation of online complaints service based on satisfaction and accuracy of targets in its implementation and public services received by the community. This study used  qualitative research with 11 informants. Data collection techniques with in-depth interviews, direct observation, documentation. The results of this study indicated that the most important thing in citizen complaints services was  the village government and local government should provide sufficient budget to carry out an innovation program because this was evidence of public service innovation that made it easy for the public to make complaints and the public as customers should begin to realize and utilize the development of information and communication technology at this time in carrying out daily activities, so that the online complaints service innovation program could be maximized as a whole. Keywords: Service innovation, complaints based online